Improving the Skills of Reading Number Notation in Grade V Students of SDK Ngorabolo - Waju, Maria Ermelinda; Dopo, Ferdinandus Bate; Fikri, Kanzul; Samino, Sena Radya Iswara (SAINTIS Publishing, 2025)
The Independent Learning Independent Campus Program is a program launched by the Ministry of Education and Culture. Research and Technology Culture (Ministry of Education, Culture, Research and Technology), which aims to improve the quality of education in various regions through the involvement of students as teachers by sending students to assigned schools. One of the main focuses of this program is to provide support to schools from elementary, junior high, and senior high schools, to develop students' basic skills, including reading number notation skills. In terms of improving the skills of reading number notation in grade 5 students, it is necessary to make efforts to improve students' competence in reading music notation. This study also aims to understand and be able to have an impact on students at SDK Ngorabolo, as well as improve their ability to read number notation. Using the Classroom Action Research (CAR) method. Data were collected through post-tests, class observations. The results of the study showed that the creative approach applied by students, such as the use of interactive media and simple tools, was able to increase students' learning motivation and understanding of number notation.